Holistic Simulation of Geotechnical Installation Processes Benchmarks and Simulations - Triantafyllidis, Theodoros (Lecture Notes in Applied and Computational Mechanics,, 2016)
This book examines in detail the entire process involved in implementing geotechnical projects, from a well-defined initial stress and deformation state, to the completion of the installation process.   The individual chapters provide the fundamental knowledge needed to effectively improve soil-structure interaction models. Further, they present the results of theoretical fundamental research on suitable constitutive models, contact formulations, and efficient numerical implementations and algorithms. Applications of fundamental research on boundary value problems are also considered in order to improve the implementation of the theoretical models developed. Subsequent chapters highlight parametric studies of the respective geotechnical installation process, as well as elementary and large-scale model tests under well-defined conditions, in order to identify the most essential parameters for optimizing the process. The book provides suitable methods for simulating boundary value problems in connection with geote chnical installation processes, offering reliable predictions for the deformation behavior of structures in static contexts or dynamic interaction with the soil.